The recovery of potassium from seawater and brines using dipicrylamine - Venn, John Garrett (Department of Chemical Engineering, 2016)
This thesis gives a literature survey of the physical and chemical properties of dipicrylamine (2,4,6,2',4',6' hexanitrodiphenylamine), its synthesis and analysis, and its use in a process for the recovery of potassium from seawater and brines. Where data is not available in the literature it is obtained by experiment. The published and experimental data are used for the design of a process using dipicrylamine for the recovery of potassium and an analysis of its economic viability. Four process steps are identified and examined. These are (i) the precipitation of the potassium salt of dipicrylamine (KDPA) from seawater or brines, (ii) the recovery of dipicrylamine from the spent seawater or brine, (iii) the conversion of KDPA to produce a potassium salt and the insoluble hydrogen form of dipicrylamine (HDPA) by reaction with an acid and (iv) the conversion of HDPA to a soluble form for recycling and reuse. It is concluded that the recovery of potassium from seawater and brines is technically viable. While the brine process is economically viable at present, the large flowrates found in process step (ii) limit the viability of the seawater process.